2019
DOI: 10.3389/fevo.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cortisol, Aggression, Dominance and Competition in Wild, West African Male Chimpanzees

Abstract: High dominance status is associated with fitness benefits in many social mammals. Yet, attaining and maintaining a high social status often comes with elevated energetic costs. Dominance rank-related exposure to energetic and psychosocial stressors is predicted to vary depending on the type of breeding system, the means a high rank is acquired and maintained, and the stability of the dominance hierarchy. Using behavioral data and urinary cortisol levels, we investigated whether a high dominance rank is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 112 publications
(228 reference statements)
3
29
0
Order By: Relevance
“…Changes in the diurnal cortisol pattern support the prediction that wild chimpanzees mobilize glucose reserves when ill and, therefore, have increased urinary cortisol levels. As observed in healthy chimpanzees during our study, urinary cortisol levels were found to decline during the day-a characteristic pattern found in healthy chimpanzees (60)(61)(62)(63), gorillas (77,78), macaques (79), and humans (77,80). The diurnal decline in urinary cortisol levels during days without symptoms is similar to the general pattern of diurnal decline observed in chimpanzees at this site (63).…”
Section: Discussionsupporting
confidence: 86%
“…Changes in the diurnal cortisol pattern support the prediction that wild chimpanzees mobilize glucose reserves when ill and, therefore, have increased urinary cortisol levels. As observed in healthy chimpanzees during our study, urinary cortisol levels were found to decline during the day-a characteristic pattern found in healthy chimpanzees (60)(61)(62)(63), gorillas (77,78), macaques (79), and humans (77,80). The diurnal decline in urinary cortisol levels during days without symptoms is similar to the general pattern of diurnal decline observed in chimpanzees at this site (63).…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, the number of publications devoted to the study of HPA axis dysfunction in humans and animals in association with disorders involving aggression, anxiety, and depressive behavior is growing. [ 2,3,7–15 ] Considerable research is carried out on HPA axis function in healthy persons and animals with high levels of anxiety or in patients with depression and anxiety disorders compared with individuals demonstrating healthy adaptive behavior. [ 2,3,7,9–13 ] Most often, healthy people with increased anxiety ratings and patients with anxiety disorders and depression demonstrated increased sensitivity of the HPA axis to stress and vulnerability to post‐stress disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, immature chimpanzees who have lost their mother play for shorter periods of time (Botero et al 2013), and play bouts escalate more frequently into aggression (van Leeuwen et al 2014). This could, in turn, lead to increased cortisol levels since in chimpanzees and other primates, aggression generally increases cortisol levels (Girard-Buttoz et al 2009;Emery Thompson et al 2010;Wittig et al 2015; but see Preis et al 2019). Furthermore, strong social relationships, which some orphans may lack, can buffer the effect of environmental stressors on cortisol secretion in primates (Young et al 2014;Wittig et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Deviations from the stereotypical patterns of high morning and low evening cortisol levels (i.e. flatter diurnal slopes) are typically interpreted as indications of pathology and HPA axis dysregulation and/or marker of chronic stress (Pruessner et al 1999;Sánchez et al 2001;Clow et al 2004;Kudielka et al 2006;Miller et al 2007). Flattening of diurnal cortisol slopes reflect a compression in the dynamic range of the HPA axis functioning (Karlamangla et al 2019) which is indicative of lowered ability to respond optimally to stressors and to down-regulate hormonal stress levels.…”
Section: Introductionmentioning
confidence: 99%